2021
DOI: 10.1186/s12896-021-00681-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of media components from different suppliers on enterokinase productivity in Pichia pastoris

Abstract: Background The aim of this study was to provide an information about the homogeneity on the level of enterokinase productivity in P. pastoris depending on different suppliers of the media components. Results In previous studies, we performed the optimisation process for the production of enterokinase by improving the fermentation process. Enterokinase is the ideal enzyme for removing fusion partners from target recombinant proteins. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…Yeast extract contains not only nitrogenous substances, but also several vitamins and minerals that are essentials for cell growth (Jacob et al, 2019;Proust et al, 2019;Yin et al, 2019). On the other hand, peptone, which is typically produced by digesting meat or other proteins, contains primarily amino acids and short peptides with less proportions of vitamin and minerals (Krahulec and S ̌afrańek, 2021). This observation agreed well with a report of Gao et al (2013) that yeast extract supported better growth than peptone, but contradict to a study of Hong et al (2011), where peptone was shown to give slightly higher CDM concentration than yeast extract.…”
Section: Resultssupporting
confidence: 87%
“…Yeast extract contains not only nitrogenous substances, but also several vitamins and minerals that are essentials for cell growth (Jacob et al, 2019;Proust et al, 2019;Yin et al, 2019). On the other hand, peptone, which is typically produced by digesting meat or other proteins, contains primarily amino acids and short peptides with less proportions of vitamin and minerals (Krahulec and S ̌afrańek, 2021). This observation agreed well with a report of Gao et al (2013) that yeast extract supported better growth than peptone, but contradict to a study of Hong et al (2011), where peptone was shown to give slightly higher CDM concentration than yeast extract.…”
Section: Resultssupporting
confidence: 87%